ABT-737 Synergizes with Chemotherapy to Kill Head and Neck Squamous Cell Carcinoma Cells via a Noxa-Mediated Pathway - Li, Rongxiu (American Society for Pharmacology and Experimental Therapeutics, 2009)
Overexpression of Bcl-X(L), an antiapoptotic Bcl-2 family member, occurs in a majority of head and neck squamous cell carcinomas (HNSCCs) and correlates with chemotherapy resistance in this disease. Overexpression of Bcl-2 is also observed in HNSCC, albeit less frequently. We have previously shown that peptides derived from the BH3 domains of proapoptotic proteins can be used to target Bcl-X(L) and Bcl-2 in HNSCC cells, promoting apoptosis. In this report, we examined the impact of ABT-737 (for structure, see Nature 435 677-681,200515902208), a potent small-molecule inhibitor of Bcl-X(L) and Bcl-2, on HNSCC cells. As a single agent, ABT-737 was largely ineffective at promoting HNSCC cell death. By contrast, ABT-737 strongly synergized with the chemotherapy drugs cisplatin and etoposide to promote HNSCC cell death and loss of clonogenic survival. Synergism between ABT-737 and chemotherapy was associated with synergistic activation of caspase-3 and cleavage of poly(ADP-ribose) polymerase. Treatment with ABT-737 plus chemotherapy resulted in dramatic up-regulation of proapoptotic Noxa protein, and small interfering RNA (siRNA)-mediated inhibition of Noxa up-regulation partially attenuated cell death by the synergistic combination. Treatment with cisplatin or etoposide, alone or in combination with ABT-737, resulted in substantial down-regulation of Mcl-1L, a known inhibitor of ABT-737 action. Further down-regulation of Mcl-1L using siRNA failed to enhance killing by the cisplatin/ABT-737 synergistic combination, indicating that chemotherapy treatment of HNSCC cells is sufficient to remove this impediment to ABT-737. Together, our results demonstrate potent synergy between ABT-737 and chemotherapy drugs in the killing of HNSCC cells and reveal an important role for Noxa in mediating synergism by these agents.